An ultrasensitive ratiometric fluorescent thermometer based on frustrated static excimers in the physiological temperature range. Issue 24 (6th March 2019) - Liang, Sen; Wang, Yuan; Wu, Xueke; Chen, Min; Mu, Lixuan; She, Guangwei; Shi, Wensheng
Abstract : We report here an ultrasensitive ratiometric fluorescent thermometer (RFT) based on the frustrated static excimers (FSEs) of DEH-PDI ( N, N ′-di(2-ethylhexyl)-3, 4, 9, 10-perylenetetracarboxylic diimide) in the physiological temperature range. Abstract : A ratiometric fluorescent thermometer (RFT) based on the frustrated static excimers (FSEs) of DEH-PDI ( N, N ′-di(2-ethylhexyl)-3, 4, 9, 10-perylenetetracarboxylic diimide) was designed and synthesized. The RFT exhibited ultrahigh sensitivities, which far exceed the existing RFTs in the physiological temperature range. The RFT also showed outstanding precisions, stability, and an obvious thermochromism in the temperature range.